Silent Reputation Builders: How Pesantren Alumni Intellectual Networks Shape Institutional Legitimacy Through Value-Based Stewardship - Ahmad Fauzi (JURNAL ISLAM NUSANTARA, 2025)
This study explores the strategic role of the Alumni Intellectual Network in building the institutional reputation of the pesantren through an informal value-based mechanism. Departing from the literature gap in the study of pesantren public relations which is still descriptive and structural, this study aims to develop a conceptual model of Stewardship-Based Public Relations (SBPR). With an interpretive qualitative approach and a critical single case study design, data was collected through in-depth interviews, document analysis, and participatory observation of one pesantren with an influential alumni history. The thematic analysis identified three main themes: (1) Informal reputation communication mechanisms carried out by alumni as gatekeepers and reputation defenders; (2) Manifestation of  alumni stewardship in the form of emotional commitment, moral obligation, and resource contribution; and (3) Adaptive challenges of public relations in managing informal networks that have symbolic authority. The findings expand on the theories  of Stewardship and Relational PR by emphasizing the importance of moral affiliation and organic communication in religious contexts. The proposed SBPR model places alumni as strategic partners in institutional legitimacy, not just public relations objects. Managerial implications show the need to change the paradigm of pesantren public relations from an administrative approach to a value-based and sustainability relationship model.